Better Presentations : A Guide for Scholars, Researchers, and Wonks - Schwabish, Jonathan (New York, NY : Columbia University Press, 2016)
Whether you are a university professor, researcher at a think tank, graduate student, or analyst at a private firm, chances are that at some point you have presented your work in front of an audience. Most of us approach this task by converting a written document into slides, but the result is often a text-heavy presentation saddled with bullet points, stock images, and graphs too complex for an audience to decipher--much less understand. Presenting is fundamentally different from writing, and with only a little more time, a little more effort, and a little more planning, you can communicate your work with force and clarity. Designed for presenters of scholarly or data-intensive content, Better Presentations details essential strategies for developing clear, sophisticated, and visually captivating presentations. Following three core principles--visualize, unify, and focus--Better Presentations describes how to visualize data effectively, find and use images appropriately, choose sensible fonts and colors, edit text for powerful delivery, and restructure a written argument for maximum engagement and persuasion. With a range of clear examples for what to do (and what not to do), the practical package offered in Better Presentations shares the best techniques to display work and the best tactics for winning over audiences. It pushes presenters past the frustration and intimidation of the process to more effective, memorable, and persuasive presentations.
Frontmatter -- Contents -- Acknowledgments -- Introduction -- Part One. Designing Your Presentation -- 1. Theory, Planning, and Design -- 2. Color -- 3. Type -- Part Two. Building Your Presentation -- 4. The Text Slide -- 5. The Data Visualization Slide -- 6. The Image Slide -- 7. The Scaffolding Slides -- Part Three. Giving Your Presentation -- 8. Presenting -- 9. The Technical Nitty-Gritty -- Conclusions -- Further Readings -- References
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed Dec. 14, 2016).
Includes bibliographical references (pages 173-177) and index.
Added to collection customer.56279.3 - Master record variable field(s) change: 072
Keywords: Business presentations; Business presentations; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Electronic books